Clinical Characteristics Of Patients With Chronic Hepatitis C Infection At Initial Presentation To Tertiary Care In An Asian Middle-income Country - Azzeri A.; Shabaruddin FH.; Tan SS.; McDonald SA.; Dahlui M.; Kamarulzaman A.; Mohamed R. (Elsevier Inc., 2024)
Value in Health Volume 20, Issue 9, October–November 2017, Page A632